ChemInform Abstract: Oxygen—Sulfur Rearrangement in the Reaction of Thiocarbamate Imidazolium Ylide with Arylaldehyde. Issue 19 (18th April 2013) - Zhao, Yingwei; Lei, Min; Yang, Lei; Han, Feng; Li, Zhen; Xia, Chungu
Abstract The ratio of the products (III) and (IV) depends on the used aldehyde and the reaction temperature.